Tanggung Jawab Pejabat Pembuat Akta Tanah (PPAT) dalam Pembuatan Akta Jual Beli Tanah Dan Implikasi Hukumnya Bagi Masyarakat Umum - Triyono, Triyono (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2019)
Certainty, order and legal protection require, among other things, in the life of public relations requires the existence of evidence that clearly determines the rights and obligations of a person as a subject of law in society. Authentic deeds as the strongest and most fulfilled evidence have a role, the need for written proof in the form of authentic deeds is increasing in line with the growing demand for legal certainty in various economic and social relations. Authentic deed which is written evidence that can be used to settle cases cheaply and quickly. PPAT is the authorized official to make the authentic deed insofar as the making of certain authentic deeds is not specific to other public officials. The authentic deed in its essence contains formal truth in accordance with what was notified to PPAT. However, PPAT has an obligation to ensure that what is contained in the PPAT Deed is truly understood and in accordance with the wishes of the parties, namely by reading it so that it becomes clear the contents of the PPAT Deed, as well as providing access to information, including access to legislation related to the parties who signed the deed. PPAT as General Officer authorized to make land deeds must have special capability in the land so that the deeds he made do not cause problems in the future, considering the deeds he made can be used as evidence of the occurrence of legal deeds of transfer of rights or cancellation of rights on land. If the cause of the problem arises because of negligence by the PPAT, then the result is that the deed has only legal force under the hand that can be canceled. Keywords: Deed, PPAT, Land Purchase